2020
DOI: 10.1007/s11606-019-05487-5
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of Four Common Diagnostic Methods for Clostridioides difficile Infection

Abstract: BACKGROUND: No studies have evaluated the costeffectiveness of single and two-step different diagnostic test strategies for Clostridioides difficile infection (CDI), including direct and indirect costs. OBJECTIVE: To evaluate the cost-effectiveness of commonly available diagnostic tests for CDI including nucleic acid amplification testing (NAAT) alone, glutamate dehydrogenase followed by enzyme immunoassay for toxin (GDH/EIA), GDH then NAAT (GDH/NAAT), and NAAT then EIA (NAAT/EIA). DESIGN: Decision tree model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Since transmission of CDI and isolation costs of CDI were both modelled [ 8 ], a missed CDI has a greater economic and clinical consequence, such that the NAAT alone pathway may remain the preferred test strategy in a setting with a lower CDI prevalence. Another cost-effectiveness analysis concluded that the NAAT alone pathway was the most cost-effective strategy for CDI diagnosis, at an incremental cost of USD 55,547 per QALY gained versus a GDH/NAAT pathway [ 23 ]. NAAT alone remained cost-effective compared with a two-step GDH/NAAT pathway over a wide range of CDI prevalence modelled (8.2–19.1%) [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since transmission of CDI and isolation costs of CDI were both modelled [ 8 ], a missed CDI has a greater economic and clinical consequence, such that the NAAT alone pathway may remain the preferred test strategy in a setting with a lower CDI prevalence. Another cost-effectiveness analysis concluded that the NAAT alone pathway was the most cost-effective strategy for CDI diagnosis, at an incremental cost of USD 55,547 per QALY gained versus a GDH/NAAT pathway [ 23 ]. NAAT alone remained cost-effective compared with a two-step GDH/NAAT pathway over a wide range of CDI prevalence modelled (8.2–19.1%) [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on Japanese clinical practice, we modeled that patients with at least three diarrheal bowel movements (Bristol stool grade ≥5) in the preceding 24 h would be tested and treated [ 22 ]. Up to two CDI recurrences were modelled for patients after the initial CDI, similar to a previous study evaluating the cost-effectiveness of CDI diagnostics in the United States [ 23 ]. Since CDI recurrences usually occur ≤60 days after the cure date of the initial CDI episode [ 24 ], the time horizon of this model was one year.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this review, nine articles reported a time horizon of one year or shorter. Only three articles used a longer time horizon in order to capture the medical consequences of developing gastric cancer [ 31 ], acute treatment failure [ 43 ] or childhood acute lymphoblastic leukemia [ 44 ]. The reviewed articles did not consider either the relapses or biofilm formation, perhaps due to the short time horizon reported in the majority of the studies.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier detection may lead to reduced infectious periods for patients, as treatment could be administered sooner. A recent study found that the most cost-effective method for diagnosis of C. difficile cost $54,500 per quality-adjusted life year (QALY) [33]. The low costs of using co-presence as a diagnostic tool would likely lead its cost per QALY to be even lower.…”
Section: Study Implicationsmentioning
confidence: 99%